ORDER PROBLEM AND THE CONCEPTUAL ATTITUDES OF MODERN THEORETICAL SOCIOLOGY - Smolyaga , Marina (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2022)
The article discusses modern conceptual perspectives in which clarification of the problem of social order is implemented. In this discussion, the following thesis is accepted: the well-known work of T. Hobbes "Leviathan..." is not just one of the explorations, albeit a classic one, on this topic, but acts as a kind of "possibility structure" for all and any subsequent attempts and experiences in this regard. This thesis is, in fact, also the task of consideration and its result (already as proven). It turns out that the Hobbesian solution is not only (and rather not) an answer to the question of order, but a brilliant working model, using which it is convenient to form various theoretical propositions. Hobbes’s "Leviathan" gives space for the appearance of cardinal themes / regions / contents of theoretical consideration in modern social philosophy and sociology. Consideration of the topos of the birth of society as an order of coexistence of human individuals-actors; the nature of the corresponding potentials; the genesis of order and its mechanisms; possibilities and conditions for the continuation of the social, i.e., ordered state and its changes, transformations, grounds for the universality (super-individuality) of the order and the relationship of these grounds to the level of individual existence, consciousness and action, etc. This demonstration is carried out through consideration of approaches to the problem of social order by Talcott Parsons, Jürgen Habermas, Nicolas Luhmann and Harold Garfunkel. In this context, the approaches of Pierre Bourdieu and Anthony Gedens are also mentioned.